Optimization of Poverty Alleviation Programs Through the Classification of Village Characteristics Around the Mandalika Special Economic Zone (SEZ) - Putra Kumara Dewa, Jhon Jhohan; Wahyuningtiyas, Loetvy; Cahyana, Alifan (Universitas Nahdlatul Ulama Sidoarjo, 2024)
The Mandalika Special Economic Zone (SEZ) in Pujut District is a tourism SEZ with rapid development, projected to absorb 194,293 workers by 2037. However, there are still 7,749 households (37.56%) categorized as pre-prosperous in the surrounding rural areas. This study analyzes rural development strategies using cluster analysis (K-means) with 5 variables: number of pre-prosperous communities, tourism facilities, trade and service facilities, capital access facilities, and SME presence. The research grouped villages into 5 clusters with different focuses: SME and trade development, capital access and trade, tourism and local employment, entrepreneurship training, and optimization of capital access for trade. This clustering aims to streamline poverty alleviation programs around the Mandalika SEZ as a regulatory improvement that pays more attention to the social and economic aspects of the surrounding communities.